The Effect of Liquidity Risk, Credit Risk, and Operational Risk on Profitability in Banking Companies in Indonesia: Case Study on Banking in Indonesia - Annisa Paramaswary Aslam; Ridfan Rifadly Abadi (PT Maju Malaqbi Makkarana, 2023)
This study aims to examine the effect of liquidity risk, credit risk and operational risk on profitability (an empirical study of Indonesian banking companies). This research is classified as causal research. This research covers several banking institutions (companies) in Indonesia from 2018 to 2022. The type of research used in this research is a descriptive verification research method with a quantitative approach. Data analysis techniques in this study were T test, F test, multiple linear regression analysis, normality analysis, heteroscedasticity analysis and multicollinearity analysis. If it is based on the results of testing using the multiple regression method with a significance level of 5%, we can conclude the results in this study, namely: (1) Credit risk has no significant effect on the profitability of banking companies in Indonesia and its significance value is 0.917 > 0.05. (2) Liquidity risk has no significant effect on the profitability of banking companies in Indonesia and its significant value is 0.853 > 0.05. (3) Operational risk has a significant positive effect on the profitability of banking companies in Indonesia and its significance value is 0.000 <0.05. 853 > 0.05. (3) Operational risk has a significant positive effect on the profitability of banking companies in Indonesia and its significance value is 0.000 <0.05. 853 > 0.05. (3) Operational risk has a significant positive effect on the profitability of banking companies in Indonesia and its significance value is 0.000 <0.05.